Textes relatifs à l’histoire de Larsa: I - Arnaud, Daniel
copies; AO.4324, copie d’une lettre; fragments de cônes de Sin- idinnam AO.25110; AO.25109; AO.25108; AO.25111; Textes de Rīm-Anum AO.7548; AO.20299; AO.20310; AO.20311.